2011
DOI: 10.1016/j.ijgo.2011.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect on ovarian reserve of laparoscopic bipolar electrocoagulation versus laparotomic hemostatic sutures during unilateral ovarian cystectomy

Abstract: Laparoscopic ovarian cystectomy is associated with a significant reduction in ovarian reserve. This is a consequence of damage to the ovarian vascularity and the removal of an increased amount of ovarian tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 23 publications
(31 reference statements)
1
38
1
1
Order By: Relevance
“…The levels of AMH 1 and 3 months after the procedure were significantly higher among patients treated with sutures according to the results of Mohamed et al 19 and Li et al 24 Takashima et al, 23 on the other hand, reported similar outcomes among the 2 groups. Three studies investigated the levels of serum AMH at 6 months following the procedure.…”
Section: Main Outcomesmentioning
confidence: 72%
See 4 more Smart Citations
“…The levels of AMH 1 and 3 months after the procedure were significantly higher among patients treated with sutures according to the results of Mohamed et al 19 and Li et al 24 Takashima et al, 23 on the other hand, reported similar outcomes among the 2 groups. Three studies investigated the levels of serum AMH at 6 months following the procedure.…”
Section: Main Outcomesmentioning
confidence: 72%
“…22,24 Bipolar electrocoagulation seems to also negatively affect the AFC. Two studies reported a negative impact during the first month, 18,19 whereas the number of studies that confirmed this observation at 3 months increased. [18][19][20]24 This effect was also observed at 6 months (3 studies 18,19,24 ) and at 12 months (1 study 18,24 ) following the procedure ( Table 3).…”
Section: Main Outcomesmentioning
confidence: 96%
See 3 more Smart Citations